Network Analysis of Internal Migration in Vietnam - Chung, Rebecca; Minh-Tu; Shu-Yi Liaw (Journal of Tropical Rural Development, 2025)
This study examines the provincial network structure within Vietnam by investigating migration patterns through the lens of spatial economics and social network analysis. Data are drawn from the Vietnam Household Living Standard Survey covering the period from 2012 to 2018, comprising 2,921 observations. A hierarchical clustering method is employed to delineate the internal migration network structure. The results reveal an asymmetrical racetrack pattern in Vietnam’s inter-regional network structure, characterized by two primary clusters-the North and the South. The southern migration cluster exhibits greater prominence, particularly due to a higher proportion of intra-regional migration. Furthermore, within these clusters, analysis of intra-regional network structure indicates an asymmetrical and megalopolitan structure, with Hanoi and Ho Chi Minh serving as the respective hubs of the northern and the southern clusters. This megalopolitan migration network provides new empirical evidence on the importance of economic agglomeration and transportation costs, as emphasized in spatial economics. Moreover, the tendency for intra-regional migration over inter-regional migration underscores the role of social network theory in understanding migration processes. The findings contribute to promote more equitable development among provinces in Vietnam, in alignment with the Sustainable Development Goal 10 on reducing inequalities.